Demodex Unmasked: The Tiny Mites Living on our Skin - Rahangdale, Vishwas; M. Unni, Mahesh; Vinay Rahangdale (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Demodex mites are microscopic arachnids that inhabit hair follicles and sebaceous glands on the face. Their prevalence increases with age and certain conditions like obesity, diabetes, and immunosuppression. While usually harmless commensals, they become pathogenic when their density exceeds 5 mites/cm² or when the skin’s balance is disrupted, leading to demodicosis. This condition manifests with various skin and ocular symptoms, including rosacea-like eruptions, blepharitis, and chalazion. Diagnosis relies on mite density assessment through methods such as standardized skin surface biopsy and dermoscopy. Factors such as prolonged mask use during the COVID-19 pandemic and immune reconstitution diseases influence mite proliferation. Treatment involves topical agents like permethrin and ivermectin, oral ivermectin or isotretinoin for resistant cases, and adjunctive therapies including intense pulsed light and microblepharoexfoliation. Management should be individualized based on severity and resistance to optimize outcomes.